The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1001/archpsyc.55.7.603
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Family Study of Anorexia Nervosa and Bulimia Nervosa

Abstract: Background:We used contemporary familyepidemiological methods to examine patterns of comorbidity and familial aggregation of psychiatric disorders for anorexia and bulimia nervosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
119
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 517 publications
(132 citation statements)
references
References 45 publications
8
119
0
Order By: Relevance
“…The diagnosis of an ED was established with the Eating Disorders Family History Interview (EDFHI) [35]. This is a structured clinical interview designed to gather detailed information for the diagnosis of AN, bulimia nervosa, binge eating disorder, or any combination of ED not otherwise specified, which has been extensively used in the study of ED patients [36]. The existence of current and previous suicide attempts was established according to data gathered from the participants, the treating physicians and the medical files.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of an ED was established with the Eating Disorders Family History Interview (EDFHI) [35]. This is a structured clinical interview designed to gather detailed information for the diagnosis of AN, bulimia nervosa, binge eating disorder, or any combination of ED not otherwise specified, which has been extensively used in the study of ED patients [36]. The existence of current and previous suicide attempts was established according to data gathered from the participants, the treating physicians and the medical files.…”
Section: Methodsmentioning
confidence: 99%
“…Despite a call for family studies in eating disorders to focus on temperament as providing the greatest utility in informing etiological processes (6), to date, most family studies of AN have focused attention on shared risk factors with other psychiatric disorders rather than with dimensional temperament styles (7)(8)(9)(10)(11). A recent review (5) identified only one study that examined dimensional temperaments and AN using a family design, which showed women with lifetime AN to be less impulsive and more restrained than their unaffected sisters (12).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, research on the causes of eating disorders has also pointed to certain personality traits [36, 37, 38, 39, 40, 41], such as low self-esteem, which may trigger eating disorders at a later age.…”
Section: Introductionmentioning
confidence: 99%